La gestión presupuestal de la inversión pública y su impacto social en el sector educación del Gobierno Regional de Loreto, periodo 2019 – 2020 - Yalta Diaz, Juana Jenice (2023)
The purpose of this research was to analyze the budget management of public investment of the Regional Government of Loreto and the social impact in the education sector during the 2019-2020 period. The study is basic, descriptive and non-experimental. According to the findings, it was determined with the significance value (observed critical value) 0.000 <0.05. We reject the null hypothesis and accept the alternative hypothesis, that is; The social impact in the education sector during the 2019-2020 budget year was not significantly impacted by the budget management of Public Investment of the Regional Government of Loreto.